Accuracy of determination of soil mechanic properties - Lazhevich, Oleg A.; Zaika, Yury V. (Journal of the Belarusian State University. Geography and Geology, 2017)
Application of conventional methods of field testing of soils, which are currently in use in the Republic of Belarus, for estimation of geotechnical conditions on building grounds of high-rise buildings as well as of the most crucial industrial and power producing objects with nonstandard characteristics, requires determining the deformational and strength properties of soils on depths of 70 meters and even more. At that, there are valuable reasons to assume that correlation ratios widely used in Belarus between results of CPT and DPT and modules of deformation may not reflect the reality and require further verification when qc and pd exceed 30 MPa. This assumption is based on our practical experience and numerous facts obtained during carrying out engineering-geological survey in Belarus. Thus, there is an objective necessity to revise our currently used correlation ratios, which in many cases do not fully reflect real deformational properties of soil.